Vitexin suppresses RANKL‐induced osteoclastogenesis and prevents lipopolysaccharide (LPS)‐induced osteolysis. Issue 10 (21st February 2019) - Jiang, Jiawei; Jia, Yewei; Lu, Xuanyuan; Zhang, Tan; Zhao, Kangxian; Fu, Ziyuan; Pang, Cong; Qian, Yu
Abstract: Osteolytic diseases are characterized by an increase in the number and/or activity of bone‐resorbing osteoclasts. Identification of natural compounds that can suppress osteoclast formation and function is crucial for the prevention and treatment of osteolytic diseases. Vitexin, a naturally‐derived flavonoid extracted from various medicinal plant species, demonstrates a broad range of pharmacological properties including anticancer and anti‐inflammatory effects. Here in this study, we showed that vitexin exerts antiosteoclastogenic effects by directly inhibiting receptor activator of nuclear factor‐κB ligand (RANKL)‐induced osteoclast formation and bone resorption in vitro and protected against lipopolysaccharide (LPS)‐induced inflammatory osteolysis in vivo. Vitexin suppressed the early activation of ERK and p38 MAPK pathways in response to RANKL thereby attenuating the downstream induction of c‐Fos and NFATc1, and abrogating the expression of osteoclast marker genes. Collectively, these results provide evidence for the therapeutic application of vitexin in the treatment of osteoclast‐mediated bone lytic diseases. Abstract : Here in this study, we showed that vitexin exerts antiosteoclastogenic effects by directly inhibiting receptor activator of nuclear factor‐κB ligand (RANKL)‐induced osteoclast formation and bone resorption in vitro and protected against lipopolysaccharide (LPS)‐induced inflammatory osteolysis in vivo. Vitexin suppressed the early activation of ERK and p38 MAPK pathways in response to RANKL thereby attenuating the downstream induction of c‐Fos and NFATc1, and abrogating the expression of osteoclast marker genes.